2022
DOI: 10.1128/spectrum.02808-22
|View full text |Cite
|
Sign up to set email alerts
|

Automated Real-Time PCR Detection of Tickborne Diseases Using the Panther Fusion Open Access System

Abstract: Since the incidence of tickborne diseases has been accelerating in the United States, automation for testing has become essential in affected regions. Unfortunately, because the need is regional, commercial test manufacturers have not yet provided answers for clinical laboratories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The Panther Fusion system open access channel has previously been utilized in direct detection or characterization of bacterial ( 41 ), parasitic ( 41 ), and viral ( 42 46 ) agents of disease and was posited in this study as an automated option for MRM determination within primary specimens testing positive for M. genitalium rRNA. Initial experimentation revealed that incubation of IVT wild-type 23S rRNA with high-concentration MRM primer and detection probe sequences, as well as an increased concentration of MgCl 2 , resulted in a propensity toward false-detections of macrolide resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The Panther Fusion system open access channel has previously been utilized in direct detection or characterization of bacterial ( 41 ), parasitic ( 41 ), and viral ( 42 46 ) agents of disease and was posited in this study as an automated option for MRM determination within primary specimens testing positive for M. genitalium rRNA. Initial experimentation revealed that incubation of IVT wild-type 23S rRNA with high-concentration MRM primer and detection probe sequences, as well as an increased concentration of MgCl 2 , resulted in a propensity toward false-detections of macrolide resistance.…”
Section: Discussionmentioning
confidence: 99%